Investigating effects of grape seed extract on neuropathic pain in the streptozotocin-induced diabetic mice. - A. Yurt; B. Köksal; P. Gürbüz; A. Yıldız; N. Vardı; E. Alçin (Medičnì Perspektivi, 2019)
Diabetes mellitus is a complicated and serious health problem involving peripheral neuropathy. This situation causes to loss of senses, tingle and pain. Diabetic peripheral neuropathy (DPN) affects 236 million people around the World. Hence there is a need to investigate alternative ways of cure focusing on DPN. Flavonoids have potential on pain due to their permeability characteristic in the capillary microcirculation system and in lowering blood pressure. Flavonoids are common in grape seed. The main flavonoids of grape seed involve proanthocyanidins which might be an effective agent in cure of pain in DPN. The purpose of this study is to investigate effects of grape seed extract on neuropathic pain in the Streptozotocin-induced diabetic mice. In the study, 50 eight-week old BALB-C strain mice in five different groups (Control, Diabetic Control, Control+25 mg/kg, Diabetes+25 mg/kg and Diabetes+50 mg/kg) were used. To induce diabetes in thirty of these animals, single dose Streptozotocin (180 mg/kg) was administered intraperitoneally. After diabetes was observed, grape seed extract (25 mg/kg and 50 mg/kg body weight) was administered by oral gavage in three groups (Control+25 mg/kg, Diabetes+25 mg/kg and Diabetes+50 mg/kg) during six weeks. At the end of the second and sixth weeks, pain threshold measurements in hot plate test were performed in line with a predetermined thermal pain model. Also the tissues of the sciatic nerve and abdominal aorta from the animals were histologically investigated. As a result hot plate measurements, pain threshold values of the animals in Diabetes+50mg/kg group significantly differed from the measurements of the animals in control group in the first measurements and from the animals in Diabetes+25 mg/kg group in the second measurements (p<0.05). However pain threshold values of the animals in Diabetes+25 mg/kg group differed significantly from the values of the animals in control+25 mg/kg group and control group. It means pain threshold values of the animals in Diabetes+50 mg/kg and Diabetes+25 mg/kg groups were significantly lower than the values of the animals in the other groups. The results of histological investigations showed that degenerations of myelin sheet and axons in diabetic control group were decreased significantly in   Diabetes+50 mg/kg and Diabetes+25 mg/kg groups. Moreover degenerations of aorta tissues of animals in diabetic group were not seen in the animals of Diabetes+50 mg/kg except for tunica adventitia inflammation. It can be said that grape seed extract decreased threshold of neuropathic pain in the Streptozotocin-induced diabetic mice and prevented degenerations of myelin sheet and axons, and aorta tissues.